Association between risk of dementia and very late-onset schizophrenia-like psychosis: a Swedish population-based cohort study. Issue 3 (25th February 2023) - Stafford, J.; Dykxhoorn, J.; Sommerlad, A.; Dalman, C.; Kirkbride, J. B.; Howard, R.
Abstract: Background: Although the incidence of psychotic disorders among older people is substantial, little is known about the association with subsequent dementia. We aimed to examine the rate of dementia diagnosis in individuals with very late-onset schizophrenia-like psychosis (VLOSLP) compared to those without VLOSLP. Methods: Using Swedish population register data, we established a cohort of 15 409 participants with VLOSLP matched by age and calendar period to 154 090 individuals without VLOSLP. Participants were born between 1920 and 1949 and followed from their date of first International Classification of Diseases [ICD], Revisions 8–10 (ICD-8/9/10) non-affective psychotic disorder diagnosis after age 60 years old (or the same date for matched participants) until the end of follow-up (30th December 2011), emigration, death, or first recorded ICD-8/9/10 dementia diagnosis. Results: We found a substantially higher rate of dementia in individuals with VLOSLP [hazard ratio (HR): 4.22, 95% confidence interval (95% CI) 4.05–4.41]. Median time-to-dementia-diagnosis was 75% shorter in those with VLOSLP (time ratio: 0.25, 95% CI 0.24–0.26). This association was strongest in the first year following VLOSLP diagnosis, and attenuated over time, although dementia rates remained higher in participants with VLOSLP for up to 20 years of follow-up. This association remained after accounting for potential misdiagnosis (2-year washout HR: 2.22, 95% CI 2.10–2.36), ascertainment bias (HR: 2.89, 95% CI 2.75–3.04), and differing mortality patterns between groups (subdistribution HR: 2.89, 95% CI 2.77–3.03). Conclusions: Our findings demonstrate that individuals with VLOSLP represent a high-risk group for subsequent dementia. This may be due to early prodromal changes for some individuals, highlighting the importance of ongoing symptom monitoring in people with VLOSLP.